Food security, farming, and climate change to 2050: challenges to 2050 and beyond - Nelson, Gerald C.; Rosegrant, Mark W.; Palazzo, Amanda; Gray I; Ingersoll C; Robertson, Richard D.; Tokgoz S; Zhu, T.; Sulser TB; Ringler, Claudia; Msangi S; You, Liangzhi (2010)
The first decade of the 21st century has brought harbingers of a troubled future for global food security. The food-price spike of 2008 led to food riots and political change in several countries. In 2010, the excessive heat and drought in Russia that led to wildfires and a grain embargo, as well as the unprecedented floods in Pakistan, signal more trouble ahead. A world population approaching 9 billion by 2050 and higher incomes in hitherto poor countries will lead to increased food demand, which means significant challenges to sustainable agricultural production.To these already daunting challenges, climate change adds more. Because food production is critically dependent on local temperatures and precipitation, any change outside the range of current conditions requires farmers to adapt their practices. The IFPRI study from which this brief is drawn, Food Security, Farming, and Climate Change to 2050, suggests that while the adaptations might be beneficial for a few farmers, for most farmers they will pose major challenges to productivity and more difficulties in managing risk. This brief highlights results from the study on possible development and climate change scenarios between now and 2050 and on what these scenarios mean for food security.